PENGUKURAN KEPUASAN MAHASISWA PADA PEMBELAJARAN KEWIRAUSAHAAN - Esti Dwi Rinawiyanti; Linda Herawati Gunawan (Asian Journal of Innovation and Entrepreneurship, 2015)
To prepare  students to be an entrepreneur, Entrepreneurship courses should be given in the  college that equip them with hard skills and soft skills of entrepreneurship. In practice, the learning of Entrepreneurship needs to be evaluated, in order to identify what is important in Entrepreneurship courses and also to measure students satisfaction with the learning so far. This study was conducted to assess the evaluation of learning of Entrepreneurship courses in a higher education, especially at the University of Surabaya by measuring the satisfaction level of students on this course. Evaluation was conducted through survey by distributing questionnaires to a number of active students who have taken the course of Entrepreneurship and Innovation (KWI) in Semester 2013/2014 at several faculties. The analysis of the level of interest could identify five important variables on that course, i.e. the practical activities need to be done to give students experience in the business, a guest lecture tells the success story to be entrepreneurs, KWI inspires many ideas for opening a new business , KWI arouse interest in entrepreneurship, as well as the courses provides an opportunity for 'learning by doing'. Through the satisfaction analysis can be listed five variables with the highest satisfaction, such as covering practical activities need to be done to give students experience in the business a guest lecture tells success story be entrepreneurs, KWI materials include hard skills and soft skills as an entrepreneur, the lecturer understand the material presented , and lecturer can motivate students to be an entrepreneur. Then from the comparison of the level of importance and level of satisfaction will be known the strenghts that should be maintained and also the weaknesses that need to be improved. The results of this study can provide an input and as a basis to increase the quality of Entrepreneurship and Innovation course further. Keywords : learning evaluation, importance level, satisfaction level, entrepreneurship